Practitioner Note 4: Inclusive social protection for forcibly displaced populations - Lucas Sato (International Policy Centre for Inclusive Growth (IPC-IG), 2022)
This Practitioners' Note is the fourth in a four-part series providing governments in the Middle East and North Africa (MENA) region and practitioners in the fields of social protection and disaster risk management (DRM) with general guidelines for future shock response informed by lessons learned from the COVID pandemic. It focuses in particular on inclusive shock-responsive social protection, which recognises that different groups of vulnerable people are impacted differently by shocks, taking into account their heterogeneous needs in the design and implementation of the response.
Keywords: 330; disaster risk management; COVID-19; social protection; MENA